2020
DOI: 10.1111/cogs.12890
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Models of Gesture and Speech Production for People With Aphasia

Abstract: People with aphasia use gestures not only to communicate relevant content but also to compensate for their verbal limitations. The Sketch Model (De Ruiter, 2000) assumes a flexible relationship between gesture and speech with the possibility of a compensatory use of the two modalities. In the successor of the Sketch Model, the AR‐Sketch Model (De Ruiter, 2017), the relationship between iconic gestures and speech is no longer assumed to be flexible and compensatory, but instead iconic gestures are assumed to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
0
9
0
1
Order By: Relevance
“…Levinson 57 befassen sich genauer mit den Phänomenen, die den Austausch von Informationen, die Regulierung des Turn Taking und bei auftretenden Problemen dann Repair-Strategien betrachtet. Levinson bezieht hier neben der verbalen auch die nonverbalen Ebenen, speziell die Gesten, mit ein, wie dies auch im Modell von de Ruiter 58 formalisiert und von de Beer et al 59 auf die kommunikativen Strategien bei Menschen mit Aphasie bezogen wird.…”
Section: Verdeckung Von Sprachbeeinträchtigungen In Der Kommunikation...unclassified
“…Levinson 57 befassen sich genauer mit den Phänomenen, die den Austausch von Informationen, die Regulierung des Turn Taking und bei auftretenden Problemen dann Repair-Strategien betrachtet. Levinson bezieht hier neben der verbalen auch die nonverbalen Ebenen, speziell die Gesten, mit ein, wie dies auch im Modell von de Ruiter 58 formalisiert und von de Beer et al 59 auf die kommunikativen Strategien bei Menschen mit Aphasie bezogen wird.…”
Section: Verdeckung Von Sprachbeeinträchtigungen In Der Kommunikation...unclassified
“…Alongside the emergence of single-word processing models, researchers such as Kendon (1980), McNeill (1992, and Goodwin (1995) emphasised the multimodal nature of information exchange, in which non-verbal channels such as gesture, facial expression, and body movement complement and supplement verbal language. Gesture has since become a fruitful area of research in aphasia (e.g., de Beer et al, 2017de Beer et al, , 2020Roper et al, 2016;van Nispen et al, 2017; see section Language use is multimodal below).…”
Section: Existing Framework Of Functional Real-world Communicationmentioning
confidence: 99%
“…The increased gesture use has been compared to communicative impairments in typical aging (>60 years of age) versus aphasic populations (Kong, Law, Kwan, et al, 2015;Kong, Law, Wat, et al, 2015). As both aging neurotypicals and aphasic populations are affected in linguistic performance tasks of fluency, word selection, and comprehension, and given that linguistic performance inclination related to gesture increases, it may be concluded that there is compensatory support by gesture in communication (Beer et al, 2020;de Ruiter, 2000). Research on the nature of the compensation suggests that it might lie in the gestural clarification or disambiguation of difficult-to-interpret speech, as well as resolving word retrieval issues (Akhavan et al, 2018;Beer et al, 2020;Kistner et al, 2019;Rose et al, 2017;van Nispen et al, 2017).…”
Section: Aphasia and Multimodal Characteristicsmentioning
confidence: 99%
“…We keep our overview of mainstream gesture research and the implications for possible "box-and-arrow" theories of gesture production in aphasia deliberately brief (see however de Beer et al, 2020), as they simply are not directly engaging with the phenomenon of multimodal prosody, i.e., the way that gesture modulations (in kinematics) relate to (acoustic markers of) speech prosody (Wagner et al, 2014). This is a pity as the prosodic modulations together with gestures may be an important semiotic means to communicate in aphasia despite impaired speech processes on other levels (syntax, lexical).…”
Section: Aphasia and Multimodal Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation